2021
DOI: 10.1101/2021.03.29.437557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A MALDI-TOF assay identifies nilotinib as an inhibitor of inflammation in acute myeloid leukaemia

Abstract: Inflammatory responses are important in cancer, particularly in the context of monocyte-rich aggressive myeloid neoplasm. We developed a label-free cellular phenotypic drug discovery assay to identify anti-inflammatory drugs in human monocytes derived from acute myeloid leukemia (AML), by tracking several biological features ionizing from only 2,500 cells using matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry. A proof-of-concept screen showed that the BCR-ABL inhibitor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
(320 reference statements)
0
1
0
Order By: Relevance
“…In another study, a label‐free cellular phenotypic drug discovery assay was developed to identify anti‐inflammatory drugs in human monocytes derived from acute myeloid leukaemia. The screen identified that the inhibitor nilotinib blocked LPS‐induced inflammatory responses (preprint: Marín‐Rubio et al , 2021 ).…”
Section: Mass Spectrometry Screening Assays For Drug Discoverymentioning
confidence: 99%
“…In another study, a label‐free cellular phenotypic drug discovery assay was developed to identify anti‐inflammatory drugs in human monocytes derived from acute myeloid leukaemia. The screen identified that the inhibitor nilotinib blocked LPS‐induced inflammatory responses (preprint: Marín‐Rubio et al , 2021 ).…”
Section: Mass Spectrometry Screening Assays For Drug Discoverymentioning
confidence: 99%